Measuring Purchase Decision Tendencies of Jakarta Special Region E-Commerce Consumer - Elang Dimas Aditya; M. Edo Suryawan Siregar; Dewi Agustin Pratama Sari (LPPM Universitas Negeri Jakarta, 2023)
The purpose of this research is to measure the influence between 1) E-Service Quality towards Purchase Intention, 2) Online Customer Review towards Purchase Intention, 3) Online Customer Review towards Purchase Decisions, 4) E-Service Quality towards Purchase Decisions, and 5) Purchase Intention towards Purchase Decision, and also to find the implications in each influence. Data collection method by using electronic questionnaire through Google Forms. Research object is Jakarta citizen that has accessed or completed at least one transaction in Tokopedia e-commerce with research conducted in April 2022 until July 2022. There are 200 samples that were analyzed using research design of Structural Equation Model (SEM) with AMOS software to process and analyze research results. Result shows that there are positive and significant effects for all of the proposed hypotheses. Result implies that even though e-Service Quality, Online Customer Reviews, and Purchase Intention, has positive and significant effects towards Purchase Decision, Tokopedia could still improves their services in several aspect such as protecting consumer purchasing behavior, increasing customer review frequency, increasing awareness for intention to purchase, and increasing overall services.